1985
DOI: 10.2307/1590681
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of Inactivated H5N2 Influenza Vaccine and Efficacy against Lethal A/Chicken/Pennsylvania/1370/83 Infection

Abstract: The hemagglutinin concentration of beta-propiolactone-inactivated influenza vaccine containing A/Duck/N.Y./189/82 (H5N2) virus was measured by single-radial-immunodiffusion (SRD) test. After administration of vaccine to chickens in Freund's complete adjuvant, vaccine efficacy was assessed by challenge with lethal A/Chicken/Penn./1370/83 (H5N2) virus. SRD potency values correlated with post-vaccination antibody levels and protection against infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 5 publications
4
26
0
Order By: Relevance
“…Measuring the HA protein content is the most direct method, but is a cumbersome and relatively insensitive process, requiring growth of large quantities of virus, concentration by ultracentrifugation and assaying with the radial single immunodiffusion test (Wood et al ., 1985;Swayne et al ., 1999). Haemagglutinating units have been used as an indirect measurement of HA protein content, but correlate poorly with HA protein content, while infectious titre has good correlation with HA content (Swayne et al ., 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Measuring the HA protein content is the most direct method, but is a cumbersome and relatively insensitive process, requiring growth of large quantities of virus, concentration by ultracentrifugation and assaying with the radial single immunodiffusion test (Wood et al ., 1985;Swayne et al ., 1999). Haemagglutinating units have been used as an indirect measurement of HA protein content, but correlate poorly with HA protein content, while infectious titre has good correlation with HA content (Swayne et al ., 1999).…”
Section: Discussionmentioning
confidence: 99%
“…After incubation at 4°C for 3 days, inactivation was confirmed by the absence of detectable infectivity after two blind passages of the formalin-treated allantoic fluid in 10-day-old embryonated chicken eggs. For the recombinant Ck/VN/C58/04 (H5N1) virus, the content of the HA protein in the allantoic fluid was standardized using a single radial immunodiffusion technique without concentration and purification (49). For the other recombinant viruses, the allantoic fluid was concentrated using a Pellicon-2 concentrator (Millipore Corporation, Bedford, MA) and purified using sucrose density gradient separation.…”
Section: Virusesmentioning
confidence: 99%
“…These results indicated that a strong B-cell memory response was generated after Salmonella HA DNA vaccination. The level of increase in HI titers after challenge can be a parameter to indicate the level of viral replication and accordingly, reflect the level of protection afforded by vaccination (35). Consistently, none of the chickens showed clinical signs and virus shedding in the SL(pHA5)ϩK group during the challenge period, but there was death and virus shedding in the SL(pHA5) and SL(p)ϩK groups (Table 2).…”
Section: Discussionmentioning
confidence: 75%